2009
DOI: 10.1590/s0100-06832009000200019
|View full text |Cite
|
Sign up to set email alerts
|

Crop sequences in no-tillage system: effects on soil fertility and soybean, maize and rice yield

Abstract: Decomposing crop residues in no-tillage system can alter soil chemical properties, which may consequently influence the productivity of succession crops. The objective of this study was to evaluate soil chemical properties and soybean, maize and rice yield, grown in the summer, after winter crops in a no-tillage system. The experiment was carried out in Jaboticabal, SP, Brazil (21 ° 15 ' 22 '' S; 48 ° 18 ' 58 '' W) on a Red Latosol (Oxisol), in a completely randomized block design, in strip plots with three re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
3
15
0
10
Order By: Relevance
“…2016 DOI: 10.1590/S0100-204X2016000900056 the roots of this species can penetrate the compacted soil layer and create biopores (Foloni et al, 2006). In the same experimental site of the present study, Marcelo et al (2009) found the highest increase in SOM content, up to the 30-cm depth, when sun hemp was used, in comparison with other second crops.…”
Section: Resultssupporting
confidence: 50%
“…2016 DOI: 10.1590/S0100-204X2016000900056 the roots of this species can penetrate the compacted soil layer and create biopores (Foloni et al, 2006). In the same experimental site of the present study, Marcelo et al (2009) found the highest increase in SOM content, up to the 30-cm depth, when sun hemp was used, in comparison with other second crops.…”
Section: Resultssupporting
confidence: 50%
“…Por 25 anos, a área foi utilizada para a produção de soja e milho em sistema convencional de preparo do solo. Em setembro de 2002, implantou-se um experimento em SSD visando à avaliação do efeito de sequências de culturas nos atributos do solo, cuja descrição detalhada foi apresentada por Marcelo et al (2009). Conforme Embrapa (2006, o solo foi classificado como Latossolo Vermelho eutrófico, textura argilosa.…”
Section: Methodsunclassified
“…Accordingly, performance of soybean growth and development was enhanced after berseem cutting as a result of optimum nutrient supply and better soil condition for growth of root and shoot of soybean crop (Billore et al, 1994). Leguminous species are known for their capacity to fix atmospheric N and narrow the C/N ratio, resulting in faster residue decomposition (Aita and Giacomini, 2003) and consequent release of accumulated N and other nutrients (Marcelo et al, 2009). …”
Section: Soybean Growth and Development At 85 Days From Sowingmentioning
confidence: 99%